(untitled) (Journal of Economic Research & Business Administration, 2015)
To assess the innovative capacity were used scorecard characterizing intellectual, financial, scientific, technical and information resources. The authors proposed the use of institutional resources, which was merged with the intellectual resource. This resource is referred to as the institutional and intellectual resource. Based on the of official statistics was analyzed indicators characterizing each resource individually. To assess of the scientific and technical resources as an indicator of the effectiveness of research and development was considered patenting activity. Identified the reasons hindering the use of information and computer technology in enterprises. Based on the analysis was assessed the innovation potential of industry in the republic. According to the analysis can be said, in spite of the fact that every year the potential incremented currently remains weak and underutilized used by industrial enterprises. Weak link in the implementation of science and the use of innovative technology companies are lack of interest, of financial resources and insufficient level of science